Coating liquid and photovoltaic front panel

By using coating liquids of fluorocarbon resin, acrylic resin and mattressing resin on the photovoltaic front panel, the problem of powdering and light transmittance reduction after long-term ultraviolet light irradiation is solved, and the effect of improving weather resistance and extending service life is achieved.

CN119662074APending Publication Date: 2025-03-21LUCKY FILM CO LTD

Patent Information

Application Number
CN202411798283.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing photovoltaic front panels are prone to pulverization and light transmittance reduction after long-term ultraviolet light exposure, resulting in insufficient weather resistance and short service life.

Method used

A coating liquid is provided, including component A and component B. Component A contains fluorocarbon resin, acrylic resin, matt resin and ultraviolet absorber. Component B contains curing agent, and a high hardness coating is formed through cross-linking reaction to improve the weather resistance and scratch resistance of the coating.

Benefits of technology

The coating formed by the coating liquid can effectively resist powdering caused by ultraviolet light, improve the weather resistance and light transmittance of the photovoltaic front panel, and extend its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177363480000081
    Figure BDA0005177363480000081
  • Figure BDA0005177363480000091
    Figure BDA0005177363480000091
  • Figure HDA0005177363490000011
    Figure HDA0005177363490000011
Patent Text Reader

Abstract

The invention discloses a coating liquid and a photovoltaic front panel. The coating liquid comprises a component A and a component B, the component A comprises the following raw materials in parts by weight: 15-35 parts of fluorocarbon resin; 20 to 40 parts of acrylic resin; 1 to 10 parts of matting resin; 1 to 5 parts of an ultraviolet absorbent; the component B comprises a curing agent, and the curing agent comprises-NCO groups. Therefore, when the coating liquid disclosed by the invention is coated on the photovoltaic front panel, powdering of the photovoltaic front panel caused by long-term ultraviolet irradiation can be effectively resisted, and meanwhile, the coating also has excellent scratch resistance, light transmission and water vapor barrier rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar cell components, and in particular relates to a coating liquid and a photovoltaic front plate. Background Art

[0002] Transparent front panels for lightweight modules are generally used on the light-receiving surface of lightweight modules to protect the cells and to isolate water vapor and provide electrical insulation. Since they need to be exposed to direct sunlight, they need to have UV resistance 5 to 7 times higher than ordinary photovoltaic back panels, as well as excellent scratch resistance and moisture and heat aging resistance. Currently, photovoltaic front panels on the market mainly include glass fiber front panels or glass fiber reinforced front panels and high-cutoff fluorine film / PET / fluorocarbon coating structure front panels, but these front panels have problems such as yellowing due to ultraviolet radiation and cracking of the fluorine film due to long-term ultraviolet aging. In addition, there are also coated photovoltaic front panels, such as patents CN209658202U, CN209658203U, CN111326601A, CN208674141U, and CN110767762A. However, these front panel weather-resistant surfaces have at least two layers of coating to achieve anti-sticking and aging resistance. The preparation process is relatively complicated, and the coated photovoltaic front panels are irradiated with ultraviolet light of 1000kwh / m 2 After that, it is easy to appear powdering and light transmittance reduction. Therefore, it is urgent to improve the powdering problem caused by long-term ultraviolet light exposure of photovoltaic front panels. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a coating liquid and a photovoltaic front panel containing the coating liquid. The coating formed by the coating liquid on the photovoltaic front panel can resist the powdering caused by long-term ultraviolet light irradiation, improve the weather resistance of the photovoltaic front panel, and extend its service life.

[0004] Therefore, in the first aspect of the present invention, the present invention provides a coating solution, comprising component A and component B; component A comprises the following raw materials in parts by weight:

[0005] 15-35 parts of fluorocarbon resin;

[0006] 20-40 parts of acrylic resin;

[0007] 1 to 10 parts of matting resin;

[0008] 1 to 5 parts of ultraviolet absorber;

[0009] Component B includes a curing agent, and the curing agent includes an -NCO group. Therefore, the coating liquid of the present invention has an excellent matting effect, can resist material pulverization caused by ultraviolet light, and has good light transmittance, scratch resistance and water vapor barrier rate.

[0010] In some embodiments, component B includes isocyanate and blocked polyisocyanate; the mass ratio of isocyanate to blocked polyisocyanate is (8:2) to (9:1).

[0011] In some embodiments, the molar mass ratio of the total -NCO groups in the B component to the total -OH groups of the fluorocarbon resin and the acrylic resin in the A component is (1-1.4):1.

[0012] In some embodiments, the coating solution satisfies at least one of the following:

[0013] (1) The fluorocarbon resin includes at least one of tetrafluoroethylene-vinyl ether copolymer, tetrafluoroethylene-vinyl ester copolymer, trifluorochloroethylene-vinyl ether copolymer and trifluorochloroethylene-vinyl ester copolymer;

[0014] (2) The Tg value of the acrylic resin is 30 to 60°C and the number average molecular weight is 20,000 to 40,000;

[0015] (3) the matt resin comprises at least one of polyester and acrylic; the refractive index of the matt resin after film formation is 1.4 to 1.5;

[0016] (4) The ultraviolet absorber includes a triazine type ultraviolet absorber.

[0017] In some embodiments, the A component further comprises the following raw materials, in parts by weight:

[0018] 1 to 5 parts of ultraviolet absorber;

[0019] Light stabilizer 0.5-2.5 parts;

[0020] 0.5-2 parts of additives;

[0021] 40 to 65 parts of solvent.

[0022] In some embodiments, the coating solution satisfies at least one of the following:

[0023] (a) Light stabilizers include hindered amine light stabilizers;

[0024] (b) The auxiliary agent includes an anti-hydrolysis agent and a leveling agent; the anti-hydrolysis agent includes carbodiimide; the leveling agent includes modified polysiloxane;

[0025] (c) The solvent includes at least one of PMA, ethyl acetate, and butyl acetate.

[0026] In a second aspect of the present invention, the present invention provides a photovoltaic front panel, comprising a weather-resistant layer; the weather-resistant layer comprises the coating liquid of the first aspect. Therefore, the photovoltaic front panel of the present invention has excellent weather resistance and can effectively resist chalking caused by ultraviolet light.

[0027] In some embodiments, the photovoltaic front panel includes: a weather-resistant layer, a first substrate layer, a first adhesive layer, a barrier layer, a second substrate layer, and a second adhesive layer stacked in sequence.

[0028] Compared with the prior art, the present invention has the following beneficial technical effects:

[0029] (1) The present invention provides a super weather-resistant and scratch-resistant coating liquid, which avoids the powdering phenomenon and transmittance loss caused by long-term ultraviolet aging of inorganic SiO2 fillers by using a matting resin and a high-efficiency ultraviolet absorber. In addition, acrylic resin and a curing agent are added to the coating liquid to improve the scratch resistance of the coating.

[0030] (2) The photovoltaic front panel of the present invention adds a barrier layer to enhance its water-blocking effect.

[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0033] Figure 1 It is a schematic diagram of the photovoltaic front panel structure of the present invention;

[0034] In the figure, 1-weather resistant layer, 2-first substrate layer, 3-first adhesive layer, 4-barrier layer, 5-second substrate layer, 6-second adhesive layer. DETAILED DESCRIPTION

[0035] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0036] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0037] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0038] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.

[0039] In a first aspect of an embodiment of the present invention, the present invention provides a coating solution, comprising component A and component B; component A comprises the following raw materials in parts by weight:

[0040] 15-35 parts of fluorocarbon resin;

[0041] 20-40 parts of acrylic resin;

[0042] 1 to 10 parts of matting resin;

[0043] 1 to 5 parts of ultraviolet absorber;

[0044] The B component includes a curing agent, and the curing agent includes -NCO groups.

[0045] In component A, the matting resin is a macromolecular substance containing micro-particles. After cross-linking with the curing agent, it forms a polymer with different refractive index, which has a matting effect. Compared with inorganic SiO2 matting powder, the matting resin has better compatibility with acrylic resin or fluorocarbon resin in the coating liquid, which also makes the coating feel softer and more textured, and has excellent light transmittance, providing the coating with good light transmittance. The -OH group contained in the fluorocarbon resin and acrylic resin undergoes a cross-linking reaction with the -NCO group in the curing agent of component B to form a polymer (RNCO+R'OH→RNHCOOR'). The polymer can increase the hardness of the coating, and the fluorocarbon resin contains CF bonds, has a high bond energy, good stability, and can improve the weather resistance of the coating. Acrylic resin has good moisture and heat resistance and wear resistance, which can improve the moisture and heat performance and scratch resistance of the coating. The ultraviolet absorber can increase the coating liquid's ability to absorb ultraviolet light, reduce the damage of ultraviolet light to the coating, and protect the coating resin and substrate. Therefore, the coating liquid of the present invention has an excellent matting effect, can resist material pulverization caused by ultraviolet light, and has excellent light transmittance, scratch resistance and water vapor barrier rate.

[0046] In some embodiments of the present invention, component B includes isocyanate and blocked polyisocyanate; the mass ratio of isocyanate to blocked polyisocyanate is (8:2) to (9:1). Thus, the matte property of the coating is further improved, and the coating resists ultraviolet light, thereby extending the service life of the material.

[0047] As examples, the mass ratios are 8:2, 8.2:1.8, 8.4:1.6, 8.6:1.4, 8.8:1.2, 9:1, etc.

[0048] In some embodiments of the present invention, the molar mass ratio of the total -NCO groups in component B to the total -OH groups of the fluorocarbon resin and acrylic resin in component A is (1-1.4) : 1. Thus, the matte property of the coating is further improved, and the UV resistance is improved, thereby extending the service life of the material.

[0049] As an example, the molar mass ratio is 1:1, 1.2:1, 1.3:1, 1.4:1, etc.

[0050] In some embodiments of the present invention, the coating liquid satisfies at least one of the following:

[0051] (1) The fluorocarbon resin includes at least one of tetrafluoroethylene-vinyl ether copolymer, tetrafluoroethylene-vinyl ester copolymer, trifluorochloroethylene-vinyl ether copolymer and trifluorochloroethylene-vinyl ester copolymer;

[0052] (2) The Tg value of the acrylic resin is 30 to 60°C and the number average molecular weight is 20,000 to 40,000;

[0053] (3) The matt resin includes at least one of polyester and acrylic; the refractive index of the matt resin after film formation is 1.4 to 1.5;

[0054] (4) The ultraviolet absorber includes a triazine type ultraviolet absorber.

[0055] Thereby, the corrosion resistance and scratch resistance of the coating can be improved.

[0056] As an example, the triazine ultraviolet absorber includes at least one of UV400, UV477, UV479, and UV405.

[0057] As an example, the Tg value is 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, etc.

[0058] As an example, the number average molecular weight is 20,000, 25,000, 30,000, 35,000, 40,000, etc.

[0059] In some embodiments of the present invention, the component A further comprises the following raw materials in parts by weight:

[0060] Light stabilizer 0.5-2.5 parts;

[0061] 0.5-2 parts of additives;

[0062] 40 to 65 parts of solvent.

[0063] According to the embodiment of the present invention, the light stabilizer in component A captures free radicals before the resin degradation reaction occurs, effectively preventing the occurrence of coating surface defects (such as loss of gloss, etc.), and improving the stability and durability of the coating; the additive can improve the surface fluidity and flatness of the coating, increase the stability of the coating liquid, etc.; the solvent plays the role of dilution, dissolution, and viscosity adjustment. Therefore, it helps to improve the weather resistance and scratch resistance of the coating liquid, improve the mechanical strength of the coating film, and extend the service life of the material.

[0064] In some embodiments of the present invention, the coating liquid satisfies at least one of the following:

[0065] (a) Light stabilizers include hindered amine light stabilizers;

[0066] (b) The auxiliary agent includes an anti-hydrolysis agent and a leveling agent; the anti-hydrolysis agent includes carbodiimide; the leveling agent includes modified polysiloxane;

[0067] (c) The solvent includes at least one of PMA, ethyl acetate and butyl acetate.

[0068] As an example, the hindered amine light stabilizer includes at least one of a piperidine derivative, an imidazolone derivative, and an azacycloalkanone derivative.

[0069] In some embodiments of the present invention, when the concentration of the ultraviolet absorber dissolved in toluene is 20 mg / L, the ultraviolet light absorbance A at 290 nm or 355 nm is ≥ 1%.

[0070] In a second aspect of the embodiment of the present invention, the present invention provides a photovoltaic front panel, comprising a weather-resistant layer; the weather-resistant layer comprises the coating liquid of the first aspect. Therefore, the photovoltaic front panel of the present invention has excellent weather resistance and can effectively resist chalking caused by ultraviolet light.

[0071] In some embodiments of the present invention, the photovoltaic front panel comprises: a weather-resistant layer, a first substrate layer, a first adhesive layer, a barrier layer, a second substrate layer, and a second adhesive layer ( Figure 1 shown).

[0072] In some embodiments of the present invention, the thickness of the weather-resistant layer is 10-20 μm.

[0073] In some embodiments of the present invention, the first substrate layer includes at least one of polyethylene terephthalate (PET), polycarbonate, and transparent glass fiber, and the thickness of the first substrate layer is 250-350 μm.

[0074] In some embodiments of the present invention, the first adhesive layer includes a polyurethane adhesive layer, and the thickness of the first adhesive layer is 5-15 μm.

[0075] In some embodiments of the present invention, the barrier layer includes an inorganic nanomaterial coating layer, and the thickness of the barrier layer is 50-200 nm.

[0076] In some embodiments of the present invention, the second substrate layer includes at least one of polyethylene terephthalate, polycarbonate, and transparent glass fiber; and the thickness of the second substrate layer is 40-100 μm.

[0077] In some embodiments of the present invention, the second adhesive layer includes component I and component II, and in parts by weight, component I includes: fluorocarbon resin, 10 to 15 parts; acrylic resin, 25 to 30 parts; matting powder, 2 to 5 parts; ultraviolet absorber, 1 to 2 parts; light stabilizer, 0.5 to 1 part; auxiliary agent, 2 to 4 parts; solvent, 50 to 55 parts; component II includes isocyanate; the thickness of the second adhesive layer is 7 to 15 μm.

[0078] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0079] In the following examples, the raw materials used are from:

[0080] The matting resins are polyester matting resin model L2018C and acrylic matting resin model Hypomer MT-2350 provided by Wuhan Yincai Technology Co., Ltd.

[0081] The acrylic resin is an acrylic resin of model HN-2604I provided by Changzhou Haina Special Adhesive Technology Co., Ltd.

[0082] The anti-hydrolysis agent is carbodiimide of model HyMax 210 provided by Langyi Functional Materials Co., Ltd.

[0083] The leveling agent is a polyether siloxane copolymer of model Glide432 provided by Shanghai Kaiyin Chemical Co., Ltd.

[0084] The isocyanate is N3390 isocyanate provided by Covestro Polymers (China) Co., Ltd.

[0085] The blocked polyisocyanate is SBU-1700 provided by Zhuotu Technology Company.

[0086] The ultraviolet absorbers are UV400, UV477, UV405, UV384-2, UV328 and UV171 provided by BASF.

[0087] The light stabilizer is UV123 hindered amine light stabilizer provided by Tianjin Lianlong New Materials Co., Ltd.

[0088] Embodiment 1:

[0089] (1) Preparation of coating solution

[0090] First, the polyester matting resin was stirred at a speed of 1000rpm / min for 30min with a stirrer for viscosity reduction treatment. Then, according to the A component formula, 50 parts of solvent (ethyl acetate), 25 parts of fluorocarbon resin (chlorotrifluoroethylene-vinyl ether), 30 parts of acrylic resin (Tg value is 30℃, number average molecular weight is 40000), 6 parts of polyester matting resin, 4 parts of ultraviolet absorber (UV400), 2 parts of light stabilizer (UV123), 1.5 parts of auxiliary agent (including 0.75 parts of anti-hydrolysis agent and 0.75 parts of leveling agent) were added to the container and stirred. The stirring speed was 1000rpm / min and the time was 60min. Then 5.7 parts of B component were added and stirred evenly. In B component, the mass ratio of isocyanate to blocked polyisocyanate was 8:2.

[0091] (2) Preparation of barrier layer

[0092] A 150 nm thick inorganic SiO2, CeO2, ZrO2 mixture coating is obtained on the 100 μm second substrate layer transparent PET by vapor deposition to form a barrier layer.

[0093] (3) Preparation of photovoltaic front panel

[0094] A first adhesive layer polyurethane adhesive with a dry thickness of 5 μm was coated on the first substrate layer (UVPET) of 350 μm, dried at 90°C, and laminated with the barrier film surface at a laminating temperature of 80°C. After pre-aging at 55°C for 2 days, the coating liquid of step (1) was coated on the other side of the first substrate layer to form a weather-resistant layer with a dry thickness of 10 μm, and dried at 150°C. A second adhesive layer with a dry thickness of 7 μm was coated on the other side of the barrier film, dried at 140°C, and aged at 55°C for 1 day to obtain a transparent photovoltaic front panel.

[0095] Embodiment 2:

[0096] The difference between Example 2 and Example 1: In the coating liquid of Example 2, the Tg value of the acrylic resin is 60°C and the number average molecular weight is 20,000; the matte resin is acrylic; the ultraviolet absorber is (UV477); the thickness of the weather-resistant layer is 20 μm, the thickness of the first substrate layer is 300 μm, the thickness of the first adhesive layer is 10 μm, the thickness of the barrier layer is 200 nm, the thickness of the second substrate layer is 40 μm, and the thickness of the second adhesive layer is 10 μm.

[0097] Embodiment 3:

[0098] The difference between Example 3 and Example 1: In the coating liquid of Example 3, the Tg value of the acrylic resin is 45°C and the number average molecular weight is 30,000; the ultraviolet absorber is 2 parts of UV405 and 2 parts of UV477; the thickness of the weather-resistant layer is 15 μm, the thickness of the first substrate layer is 250 μm, the thickness of the first adhesive layer is 15 μm, the thickness of the barrier layer is 50 nm, the thickness of the second substrate layer is 70 μm, and the thickness of the second adhesive layer is 15 μm.

[0099] Embodiment 4:

[0100] The difference between Example 4 and Example 1: In the coating liquid of Example 4, the Tg value of the acrylic resin is 35°C and the number average molecular weight is 20,000; the matte resin is acrylic; the thickness of the weather-resistant layer is 15 μm, the thickness of the first substrate layer is 275 μm, the thickness of the first adhesive layer is 15 μm, the thickness of the barrier layer is 200 nm, the thickness of the second substrate layer is 100 μm, and the thickness of the second adhesive layer is 15 μm.

[0101] Embodiment 5:

[0102] The difference between Example 5 and Example 1: In the coating liquid of Example 5, the Tg value of the acrylic resin is 60°C and the number average molecular weight is 20,000; the ultraviolet absorber is UV477; the thickness of the weather-resistant layer is 20 μm, the thickness of the first substrate layer is 300 μm, the thickness of the first adhesive layer is 10 μm, the thickness of the barrier layer is 200 nm, the thickness of the second substrate layer is 40 μm, and the thickness of the second adhesive layer is 10 μm.

[0103] Comparative Example 1:

[0104] The difference between Comparative Example 1 and Example 1 is that in the coating solution of Comparative Example 1, the Tg value of the acrylic resin is -3°C and the number average molecular weight is 7,000.

[0105] Comparative Example 2:

[0106] The difference between Comparative Example 2 and Example 2: In the coating liquid of Comparative Example 2, the ultraviolet absorber is UV384-2.

[0107] Comparative Example 3:

[0108] The difference between Comparative Example 3 and Example 3 is that in the coating solution of Comparative Example 3, the ultraviolet absorber is a compound of two common ultraviolet absorbers, UV328 and UV171.

[0109] Comparative Example 4:

[0110] The difference between Comparative Example 4 and Example 4 is that the photovoltaic front sheet of Comparative Example 4 does not have a barrier layer.

[0111] Comparative Example 5:

[0112] The difference between Comparative Example 5 and Example 5 is that the matting resin in Comparative Example 5 uses inorganic matting powder SiO2.

[0113] The specific parameters of each embodiment and comparative example are shown in Table 1 below.

[0114] Table 1 Parameter setting table of embodiments and comparative examples

[0115]

[0116] (Note: When the UV absorber is dissolved in toluene and the concentration is 20 mg / L, the absorbance ≥ 1 is a high-efficiency UV absorber, and the absorbance < 1 is a common UV absorber)

[0117] Performance Test:

[0118] 1. Pencil hardness of weather-resistant surface

[0119] Refer to GB / T 6739-2006.

[0120] (1) Use a special mechanical pencil sharpener to sharpen each pencil, removing only the wood and leaving the pencil lead intact and smooth.

[0121] (2) Hold the pencil vertically and keep it at a 90° angle to the sandpaper. Move the pencil back and forth on the sandpaper to grind the tip of the pencil lead flat (at a right angle). Continue moving the pencil until you get a smooth, round cross-section with no chips or nicks on the edges. Repeat this step every time you use the pencil.

[0122] (3) Place the photovoltaic front panel sample on a horizontally placed glass sheet with the weather-resistant surface facing upward. Insert a pencil naturally into the round hole of the hardness tester and let it naturally droop to the surface of the film. The load used by the pencil hardness tester is 1000g, and then tighten the fixing knob.

[0123] (4) Push the instrument at a speed of 1.0 mm / s to move a distance of 10 mm, and repeat this process five times.

[0124] (5) Use an eraser to wipe the hardened surface. When all debris on the hardened surface is wiped off, the damage is easier to assess.

[0125] (6) Observe the middle of the sample to see if there is any scratch. If not, repeat the experiment with a pencil of higher hardness.

[0126] (7) The sample is tested three times in parallel. If the results are different, retest.

[0127] 2. Standard UV 1000kwh / m 2 performance

[0128] (1) Place the photovoltaic front panel with the weather-resistant surface facing up in a standard UV aging box, set the sample surface temperature to 55-65°C, and the irradiation intensity to 200W / m 2 ·h, of which the ultraviolet radiation with a wavelength between 280 and 320nm accounts for 3% to 10% of the total radiation; the total radiation is 1000kwh / m 2 Then gently rub the surface of the weather-resistant layer with your finger to observe whether it is powdered. If there is no white powder, it is NO. If there is white powder, it is YES. Use a UV spectrophotometer to test the transmittance of 400-1000nm.

[0129] 3. Water vapor transmission rate

[0130] The water vapor transmission rate is carried out according to GB / T 26253. The test conditions are: temperature 38℃±2℃, humidity 90%.

[0131] Test results:

[0132] The performance test results of each embodiment and comparative example are shown in Table 2.

[0133] Table 2 Performance test results of various embodiments and comparative examples

[0134]

[0135] It can be seen from Table 2 that the weather-resistant layers of implementations 1-5 can resist the powdering caused by ultraviolet light, and have excellent hardness, water vapor permeability and light transmittance. Ordinary acrylic resin is used in Comparative Example 1, resulting in insufficient hardness. Ordinary ultraviolet absorbers with an absorbance of less than 1 are used in Comparative Example 2, resulting in its inability to resist ultraviolet light and causing powdering. Two ordinary ultraviolet absorbers with an absorbance of less than 1 are used in Comparative Example 3, which still cannot resist ultraviolet light and cause powdering, and also have a certain effect on its light transmittance, resulting in a low light transmittance. In Comparative Example 4, since no barrier layer is set, water vapor can easily pass through. In Comparative Example 5, the matting resin uses inorganic matting powder SiO2. Compared with the embodiment, the inorganic matting powder SiO2 has poor compatibility with the resin, resulting in powdering after ultraviolet light irradiation.

[0136] This indicates that the weather-resistant layer formed by the coating liquid of the present invention on the photovoltaic front panel can effectively resist the powdering caused by ultraviolet light, while also improving the scratch resistance, light transmittance and water vapor barrier effect of the coating, thereby improving the weather resistance of the coating and effectively extending the service life of the material.

[0137] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0138] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A coating liquid, characterized in that: It comprises component A and component B; in parts by weight, the component A comprises the following raw materials: 15-35 parts of fluorocarbon resin; 20-40 parts of acrylic resin; 1 to 10 parts of matting resin; 1 to 5 parts of ultraviolet absorber; The B component includes a curing agent, and the curing agent includes an -NCO group.

2. The coating solution according to claim 1, characterized in that The B component includes isocyanate and blocked polyisocyanate; the mass ratio of the isocyanate to the blocked polyisocyanate is (8:2) to (9:1).

3. The coating solution according to claim 1, characterized in that The molar mass ratio of the total -NCO groups in the B component to the total -OH groups of the fluorocarbon resin and the acrylic resin in the A component is (1-1.4):

1.

4. The coating solution according to claim 1, characterized in that The coating liquid satisfies at least one of the following: (1) The fluorocarbon resin comprises at least one of tetrafluoroethylene-vinyl ether copolymer, tetrafluoroethylene-vinyl ester copolymer, trifluorochloroethylene-vinyl ether copolymer and trifluorochloroethylene-vinyl ester copolymer; (2) The acrylic resin has a Tg value of 30 to 60° C. and a number average molecular weight of 20,000 to 40,000; (3) The matte resin comprises at least one of polyester and acrylic; the refractive index of the matte resin after film formation is 1.4 to 1.5; (4) The ultraviolet absorber includes a triazine ultraviolet absorber.

5. The coating solution according to claim 1, characterized in that In parts by weight, the component A also includes the following raw materials: Light stabilizer 0.5-2.5 parts; 0.5-2 parts of additives; 40-65 parts of solvent.

6. The coating solution according to claim 5, characterized in that The coating liquid satisfies at least one of the following: (a) the light stabilizer comprises a hindered amine light stabilizer; (b) the auxiliary agent includes an anti-hydrolysis agent and a leveling agent; the anti-hydrolysis agent includes carbodiimide; the leveling agent includes modified polysiloxane; (c) The solvent includes at least one of PMA, ethyl acetate and butyl acetate.

7. A photovoltaic front panel, characterized in that: It comprises a weather-resistant layer; the weather-resistant layer comprises the coating liquid according to any one of claims 1 to 6.

8. The photovoltaic front panel according to claim 7, characterized in that: The photovoltaic front plate comprises: a weather-resistant layer, a first substrate layer, a first adhesive layer, a barrier layer, a second substrate layer and a second adhesive layer which are stacked in sequence.

Citation Information

Patent Citations

  • Front panel film of solar cell, manufacturing method thereof and solar cell

    CN110767762A

  • Photovoltaic module panel, preparation method thereof and photovoltaic module

    CN111326601A

  • Solar cell front bezel membrane and solar cell

    CN208674141U

  • Packaging front plate

    CN209658202U

  • Packaging front plate

    CN209658203U

Cited By

  • Coating film capable of blocking infrared rays and ultraviolet rays as well as preparation method and application of coating film

    CN120209382A

  • Porphyrin-based protective coating for photovoltaic panel as well as preparation method and application of porphyrin-based protective coating

    CN121045885A